Reproductive parameters of Potamorhina altamazonica (Cope,1878) “Llambina”, in the middle basin of the Putumayo River, Loreto, Peru - Yumbato C., Hiro; Ríos I., Enrique; Puicón N., Victor; Augusto Murrieta-Morey, German (Manglar, 2024)
The llambina (Potamorhina altamazonica) is one of the most commercialized scale fish in the middle and upper basin of the Putumayo River in the tri-national zone between Colombia, Ecuador and Peru. However, despite its importance, there is very little biological information on this species to guide fisheries management in this sector of the Peruvian Amazon. For this purpose, 336 specimens collected in fish outlets and fishing areas near the ‘El Estrecho’ City between 2020 and 2021 were analyzed. The reproductive parameters were determined, as well as the sex ratio, the first size at sexual maturity and the gonadosomatic index. Among the main results, it was observed that the sex ratio of P. altamazonica showed significant differences (x2 0,05) assuming an overall ratio of 1,9:1 in favor of females. It is recommended to establish the minimum catch size at 22,5 cm (LT) for females and 22,1 cm for males, respectively. The gonadosomatic index of P. altamazonica was higher between October and February. It is concluded that the reproduction parameters are influenced by the hydrological period of the Putumayo River.